2020
DOI: 10.1093/mnras/staa271
|View full text |Cite
|
Sign up to set email alerts
|

Secular evolution of close-in planets: the effects of general relativity

Abstract: Pairs of planets in a system may end up close to their host star on eccentric orbits as a consequence of planet-planet scattering, Kozai or secular migration. In this scenario, general relativity and secular perturbations have comparable timescales and may interfere with each other with relevant effects on the eccentricity and pericenter evolution of the two planets. We explore, both analytically and via numerical integration, how the secular evolution is changed by general relativity for a wide range of diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…From the study of such systems, our results indicated that the efficiency of formation of HJ candidates from high-eccentricity mechanisms is about 3.3% (2.9%) in numerical experiments without (with) GR effects. The slightly smaller number of HJ candidates in simulations with GR is consistent with studies developed by Marzari & Nagasawa (2020), who showed the GR can significantly reduce the oscillations of eccentricity of close-in planets in their secular evolution. We remark that the percentages of HJ candidates produced in the present investigation are also in a good agreement with previous works that focused on different high-eccentricity mechanisms (see Beaugé & Nesvorný 2012;Petrovich 2015b;Muñoz et al 2016;Petrovich & Tremaine 2016;Wang et al 2017;Teyssandier et al 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…From the study of such systems, our results indicated that the efficiency of formation of HJ candidates from high-eccentricity mechanisms is about 3.3% (2.9%) in numerical experiments without (with) GR effects. The slightly smaller number of HJ candidates in simulations with GR is consistent with studies developed by Marzari & Nagasawa (2020), who showed the GR can significantly reduce the oscillations of eccentricity of close-in planets in their secular evolution. We remark that the percentages of HJ candidates produced in the present investigation are also in a good agreement with previous works that focused on different high-eccentricity mechanisms (see Beaugé & Nesvorný 2012;Petrovich 2015b;Muñoz et al 2016;Petrovich & Tremaine 2016;Wang et al 2017;Teyssandier et al 2019).…”
Section: Discussionsupporting
confidence: 89%
“…In other words, the efficiencies of production of HJ candidates were 3.32% and 2.89% with respect to the total number of systems with dynamic instability events in No-GR and GR simulations, respectively. This reduction in the number of HJ candidates in the GR scenario may be explained by the fact that GR contributes to reducing the periods and amplitudes of the eccentricity oscillations of the planets in secular evolution as Marzari & Nagasawa (2020) recently showed.…”
Section: Efficiencies Of High-eccentricity Mechanisms In the Producti...mentioning
confidence: 79%
“…Moreover, we see that the eccentricity excitation of the inner planet is reduced with the GR contribution (see e.g. Migaszewski & Goździewski 2009;Sansottera et al 2014;Marzari & Nagasawa 2020). For i mut = 50 • (bottom panels), we note an additional consequence: the libration of the angle ω 1 (bottom left) vanishes when considering relativistic corrections (bottom right).…”
Section: Influence Of Gr On the Extent Of The Lk Regionmentioning
confidence: 87%
“…By using the same approximation but limited to the octupole level, Naoz et al (2013) discussed how GR can suppress or excite the eccentricities in triple-star systems. More recently, employing linear secular theory, Marzari & Nagasawa (2020) showed that, for coplanar two-planet systems with a close-in planet, a significant damping of the eccentricities of the inner and outer planets occurs when GR is included, which implies that systems with a chaotic behaviour caused by mutual interactions between the planets could actually have a stable evolution thanks to GR effects.…”
Section: Introductionmentioning
confidence: 99%
“…Precession due to General Relativity (GR) can become a significant effect for planets orbiting close to their host stars, and in particular can influence the secular interactions within planetary systems, as shown for example in the recent study by Marzari & Nagasawa (2020). As discussed in section 4.3.1, the dominant effect that perturbs the inner systems in our study is the mutual scattering of outer giants, such that during pericentre passage they enter the inner system and cause strong scattering of the planets there.…”
Section: Relativistic Precessionmentioning
confidence: 99%